2020
DOI: 10.1080/20009666.2020.1740507
|View full text |Cite
|
Sign up to set email alerts
|

A resident-led initiative to improve patient safety event reporting in an internal medicine residency program

Abstract: Background: Despite the Clinical Learning Environment Review's recommendations of their use, patient safety event reporting systems are underutilized by residents. Objective: We aimed to identify perceived barriers to event reporting amongst internal medicine residents and implement a targeted quality improvement initiative to address the identified barriers and increase overall resident event report rates. Methods: A total of 94 Internal Medicine (IM) residents participated in the educational intervention in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…These programs used various strategies to increase resident-identified patient safety and quality concerns and to engage residents in analyzing these events. [6][7][8][9][10][11][12][13] However, none of the prior studies indicated that all resident event report submissions would be reviewed and that feedback would be sent to the submitting residents on how their concerns would be addressed-a key provision of our program.…”
Section: Discussionmentioning
confidence: 99%
“…These programs used various strategies to increase resident-identified patient safety and quality concerns and to engage residents in analyzing these events. [6][7][8][9][10][11][12][13] However, none of the prior studies indicated that all resident event report submissions would be reviewed and that feedback would be sent to the submitting residents on how their concerns would be addressed-a key provision of our program.…”
Section: Discussionmentioning
confidence: 99%